A cross sectional study on school absenteeism among female adolescents during menstruation in the rural Jharkhand - ., Vidyasagar; Jilani, Kashmira (International Journal Of Community Medicine And Public Health, 2020)
Background: Girls especially during menstruation are likely to be affected in different ways by inadequate water, sanitation and hygiene conditions in schools, and this may contribute to unequal learning opportunities. For example, lack of adequate, separate private and secure toilets and washing facilities may discourage parents from sending girls to school. The objective of the study was to find the relation between wash facility and school absenteeism among the girls from a rural community of Jharkhand. Methods: Community based cross sectional study at the rural area among the school girls of classes 8 to 10. Pre tested semi structured questionnaire was used. Data entry at MS Excel and data analysis was done using Statistical Package for Social Sciences (SPSS) software, version 20.0. Results: The mean age at menarche was 12.13 years. At school, separate wash area for girls was present in most of the cases 228 (61.1%). About 39 (9.9%) participants did not attend school during the menstrual days. Of this 29 (74%) believed that lack of separate wash at schools was a reason. Conclusions: Presence of separate wash area for girls at school was significantly (p-value<0.001) associated with good attendance during menstruations (96%).